Screening for ovarian cancer: Evidences - Shrestha, Binuma; Acharya, Bijaya Chandra (Nepalese Journal of Cancer, 2017)
Cancer of the ovary is a leading cause of death among women. Early stage disease are not evident for the incumbent nature of disease in the abdominal cavity. When ovarian cancer is detected and treated while it is still confined to the ovary (stage I), the 5-year survival rate is approximately 90%, but 33% when the disease is diagnosed at stage III or IV. So screening had role in down staging the disease and improve survival. Evidence still does not support screening in average risk women but annual gynecologic examination with pelvic examination is recommended for preventive healthcare. Screening in women with increased risk and inherited risk result in a decrease in the number of deaths in women. For women with mutations in BRCA2, ovarian cancer screening should be initiated between ages 35 and 40.